Mixing medicines : ecologies of care in Buddhist Siberia - Chudakova, Tatiana (Thinking from elsewhere., 2021)
Mixing Medicines is an ethnography of Russian medicine's attempts to recuperate indigenous therapeutic traditions associated with the state's ethnic and religious minorities. Based in Buryatia, a traditionally Buddhist region in southeastern Siberia, the book traces the uneven terrains of encounter between indigenous healing, the state, and transnational medical flows.